The Elusive “Switch Process” in Bipolar Disorder and Photoperiodism: A Hypothesis Centering on NADPH Oxidase-Generated Reactive Oxygen Species Within the Bed Nucleus of the Stria Terminalis - Raitiere, Martin N. (Frontiers in Psychiatry, 2022)
One of the most striking and least understood aspects of mood disorders involves the “switch process” which drives the dramatic state changes characteristic of bipolar disorder. In this paper we explore the bipolar switch mechanism as deeply grounded in forms of seasonal switching (for example, from summer to winter phenotypes) displayed by many mammalian species. Thus we develop a new and unifying hypothesis that involves four specific claims, all converging to suggest that the bipolar switch process has deeper affinity to the light-sensitive (photoperiodic) infrahuman switch sequence than has been appreciated. First, rapid eye movement (REM) sleep in both human and subhuman plays a key role in probing for those seasonal changes in luminance and length of day that trigger the organism’s characteristic involutional response (in certain animals, hibernation) to shorter days. Second, we claim that this response requires the integrity of a neural circuit centering on the anterior bed nucleus of the stria terminalis. Third, we propose that a key molecular mediator of the switch process involves reactive oxygen species (ROS) of a particular provenance, namely those created by the enzyme NADPH oxidase (NOX). This position diverges from one currently prominent among students of bipolar disorder. In that tradition, the fact that patients afflicted with bipolar-spectrum disorders display indices of oxidative damage is marshalled to support the conclusion that ROS, escaping adventitiously from mitochondria, have a near-exclusive pathological role. Instead, we believe that ROS, originating instead in membrane-affiliated NOX enzymes upstream from mitochondria, take part in an eminently physiological signaling process at work in all mammals. Fourth and finally, we speculate that the diversion of ROS from that purposeful, genetically rooted seasonal switching task into the domain of human pathology represents a surprisingly recent phenomenon. It is one instigated mainly by human-caused, entirely extragenetic, modifications of the environment.